Apolipoprotein E Polymorphism and Lipid Metabolism Disorders in Children with Cholelithiasis - Ye.V. Shutova (Zdorovʹe Rebenka, 2016)
Relevance. The incidence of cholelithiasis in children in Ukraine has increased from 0.1–1 to 4.8 % in the structure of biliary pathology [6, 9, 13]. Rising the incidence of cholelithiasis in childhood is obvious, but the reasons are not clear. The genetic factors of this disease in childhood are underinvestigated. Objective: to study the associations of apolipoprotein (Apo) E subclasses and parameters of lipid spectrum in children with cholelithiasis. Materials and methods. 44 children (24 girls and 20 boys) with cholelithiasis aged 5–18 years were under supervision. The study involved patients with stage I (n = 23) and stage II (n = 21) cholelithiasis. Genotyping has been performed by Apo E alleles using polymerase chain reaction method (Termocycler test system). Lipid profile has been assessed in different Apo E phenotypes. The findings were statistically processed using STATISTICA 6.0 software package. Results. It has been found that low-density lipoprotein level was significantly different in E3/E4 and E4/E4 phenotypes (pk-w < 0.01). Very-low-density lipoprotein levels differed most significantly in E3/E3 and E3/E4 phenotypes (pk-w = 0.02). So, very-low-density lipoprotein values in E3/E4 phenotype were significantly higher than in E3/E3 phenotype (0.89 ± 0.12 mmol/l versus 0.36 ± 0.06 mmol/l, pu < 0.05). In patients with E4/E4 phenotype, atherogenic index was significantly higher (3.45 ±  0.34 c.u.) than in E3/E3 phenotype (2.17 ± 0.12 c.u., pu < 0.05) and E3/E4 phenotype (1.84 ± 0.24 c.u., pu < 0.05). Conclusion. Analysis of lipid spectrum in children with cholelithiasis and different Apo Е phenotypes gives an indication of genetic susceptibility to lipid metabolism disorders. Marker of increased risk for cholelithiasis development is E4/E4 phenotype.